Diagnóstico de Clamidiosis en aves de la ciudad de General Pico, La Pampa, Argentina (Veterinary Science, 2017)
Clamidiosis is a zooantrophonosis that affects birds, producing important clinical synthoms in human beings. 120 conjuntival secretion samples were taken from psitacid birds of particular houses and pets shop, in General Pico, La Pampa with the purpose of detecting the presence of this etyologic agent.To such aim, cell diagnostic techniques (Giemsa and direct Inmunofluorescence) were used as first tests, confirming themselves by the Polymerase Chain Reaction (PCR).One concludes that the disease is present in the city.
Keywords: Diagnosis; Clamidophila psittaci; Birds